Grape antioxidants - influence of processing parameters on their content and activity - Ružić, Iva (visokošolska dela, 2012)
Grapes and wine production residuals, containing grape skins, seeds and stems,represent important sources of phenolic compounds. Red wines are rich inphenolic antioxidants while white wines generally show lower (poly)phenolic content and antioxidant activity. The main difference in the production of white and red wines is the fermentation step. The fermentation of red grapes includes maceration, i.e. it takes place in both liquid and solid parts of thegrape. In the case of white wines, the must is clarified before the fermentation starts, cultured yeasts are added to convert the must to wine andantioxidant sulfur dioxide is inserted to protect the wine. The objective of the PhD research was to study antioxidant potential of white grape phenolics both in raw material and fermentation products. First, the standardsof phenolic compounds commonly found in white grapes and wines were tested for their antioxidant and antiradical activity. All tested compounds except apigenin showed strong antioxidant and antiradical properties. Afterwards, conventional solid-liquid extraction (CE) and pressurized liquid extraction (PLE) of phenolic compounds from grape seeds were performed. The optimal extraction conditions were investigated and extracts were analyzed in order to determine their total phenolic content, individual phenolic compoundsand antiradical potential. Two different drying methods (hot air and freeze drying) were applied to the seeds. Solvent efficiencies of water, ethanol and water-ethanol mixtures were compared at different temperatures. Inaddition, supercritical fluid extraction (SFE) with CO2 was investigated as the technique for the recovery of phenolic compounds and for the pretreatment of white grape seed samples. Both CE and PLE gave extracts rich in phenolic compounds with good antiradical properties and, generally, the best results were obtained with PLE at 130°C. At the end, the influence of maceration process on the content and the activity of grape phenolic antioxidants in white wines was studied. For such a purpose, six commercially available macerated white wines from Italy and Croatia were analyzed. In addition, eightnon-macerated wines from the same region and variety were studied and compared to macerated wines. The experiments have shown that the maceration process increases the total phenolic content and antiradical activity of the wine. It enables the production of white wines rich in phenolic compounds and with strong antiradical properties in completely natural way using only the grapes and without addition of any chemical agents.
Keywords: Antioksidanti; antioksidativna aktivnost; Bela vina; Belo grozdje; Disertacije; grozdje; maceracija; polifenoli; vino